THE INFLUENCE OF THE AUDIT OPINION, THE ORIGINAL AREA OF REVENUE (PAD) AND THE EQUALIZATION FUND (DP) TO REGIONAL FINANCIAL PERFORMANCE (Empirical Studies On Local Governments That Exist In Central Java) - Muhammad Ar Rozy; Provita Wijayanti (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2014)
This research aims to find out whether the audit Opinion on The financial statements, the original area of Revenue (PAD) and the Equalization Fund (DP) has an impact on the financial performance of the region. Measuring financial performance in this area using the ratio of efficiency. The Data analyzed in this study using a sample town and district in Central Java province with reference to the financial report of The year 2011 has been published. In this research hypothesis testing is carried out using classic assumption test and test the hypothesis by using multiple linear regression analysis testing. A classic assumption test results and test hypothesis suggests that there are influences between the Audit Opinion, the original Area and revenue (PAD) against the financial performance of the region. Equalization Fund (DP) do not affect significantly the financial performance of the region.